Evaluation of the phytoremediation capacity and effects on the proteome in response to stress by Cd and Pb in species of Paspalum fasciculatum Willd (Ex Flüggé) (Poaceae) grown in a mining soil from northern Colombia (2020)
Cadmium and lead are the most toxic heavy metals that exist in nature; soil contamination by these metals is a global concern, industrial development, overpopulation, mining, burning of fossil fuels, use of wastewater in agricultural crops, inadequate disposal of solid waste, forest fires among other activities, are its main sources of pollution. The removal of xenobiotics from the soil is one of the main global environmental concerns. Phytoremediation is one of the main alternatives to this problem, in which many species of plants with specific characteristics play an important role. The aim of this work is to evaluate the phytoremediation capacity of Paspalum fasciculatum Willd. Ex. Flüeggé (Poaceae) in soils contaminated with high concentrations of cadmium and lead coming from mining areas of northern Colombia (Mine “El Alacrán”, department of Córdoba), under greenhouse conditions. Additionally, the phytotoxic effects of these metals in P. fasciculatum and the bioavailabily of the metals in the soil during this process were determined. Redox proteomic techniques were used to measure the oxidative effects of Cd and Pb exposure during the growth of P. fasciculatum, the carbonyl index was used to quantify the global oxidative damage by the proteomes of leaves and roots of P. fasciculatum with its effects on biomass and accumulation patterns. Quantitative proteomics techniques were also used to determine protein expression in these plants, which allowed us to establish the possible molecular defense mechanisms induced by the toxic stress of lead in the plant. With this research, it is expected to obtain a wild plant with the capacity to remove lead and cadmium from contaminated soils, especially of mining origin, to contribute in part to remediate mining contamination in the country and globally. Furthermore, to know the molecular mechanisms involved in the tolerance of P. fasciculatum during the phytoremediation process, through the differential expression of its proteins.